P123 Use of blood eosinophils to predict outcomes under inhaled maintenance treatment in steroid-naïve COPD patients in primary care: new user cohort study using the clinical practice research datalink. (December 2018) - Ashdown, HF; McFadden, E; Thomas, DM; Pavord, ID; Butler, CC; Bafadhel, M; Smith, M
Abstract : Introduction and objectives: Blood eosinophils are a potentially useful biomarker to guide inhaled corticosteroid (ICS) treatment in COPD. We aimed to investigate whether blood eosinophil count predicts the effect of maintenance treatment with ICS versus non-ICS in routine primary care. Methods: We used routinely collected data from UK primary care in the Clinical Practice Research Datalink, linked with Hospital Episode Statistics. Eligible patients were ≥40 years with COPD, history of smoking and diagnostic spirometry, not already treated with ICS, starting a new inhaled maintenance medication (intervention group: ICS; comparison group: long-acting bronchodilator, non-ICS) between 2005 and 2015. Primary analysis used the most recent blood eosinophil count in the two years before the new treatment, divided into high (≥150/µL) and low (<150/µL) groups. Primary outcome was time-to-first-exacerbation event after maintenance treatment initiation, compared between ICS and non-ICS groups, stratified by blood eosinophil group. Cox regression using co-variates likely to contribute to confounding by indication, including severity and baseline exacerbation frequency, investigated the interaction of blood eosinophils. Results: Of 8452 eligible patients, 50.2% initiated an ICS (68.0% high eosinophil) and 49.8% a non-ICS treatment (67.3% high eosinophil), with no difference in eosinophils between treatment groups (p=0.486). Risk of exacerbation was higher in patients prescribed ICS than non-ICS, but with a lower risk seen in those with high eosinophils (hazard ratio 1.12, 95% CI 1.06–1.19) than low eosinophils (1.30, 95% CI 1.20–1.43) (p-value for interaction, 0.005) (see figure 1). The association was attenuated but remained significant (p=0.02) in a model adjusted for co-variates including severity and baseline exacerbation frequency. Conclusions: This is the first study demonstrating significant predictive effect of blood eosinophils on ICS treatment outcomes in primary care, in a very large COPD population studied. In contrast to results from trials, the ICS group had worse outcomes, possibly due to residual confounding by indication. Blood eosinophils may be a low cost and acceptable way to identify patients most likely to benefit from ICS. Further work is needed to determine thresholds in primary care.